Trabalho docente e formação de professores para o uso de tecnologias digitais a partir da pandemia de COVID-19 em uma escola do campo - Campos, Camila Dinat (2023)
The research investigated the use of digital educational tools during remote teaching in the COVID-19 pandemic and the continuation of these practices upon the return to in-person classes in a rural school, resulting in an educational product in the form of an ebook—a guide with digital tools for use in teaching. The overall objective of this research was to analyze pedagogical practices and their potentials, based on participation in a focus group related to the use of digital technologies in the context of remote and in-person teaching during and after the COVID-19 pandemic. Specific objectives include discussing government policies for implementing remote and hybrid teaching in the state education system of Rio Grande do Sul, analyzing students' access to remote and hybrid teaching, and identifying the digital technologies adopted during the remote period and their continued use upon the return to in-person classes. The underlying concepts of the research are teacher training and cyberculture, rural education, remote teaching, and digital technologies in education. The methodology used was action research, aiming to achieve concrete actions and transformations in the social field. The choice of action research is related to the intention to transform the reality of the researched environment and the collective participation of the subjects involved in the research. The ebook titled "Practical Guide with Digital Tools to Aid Teaching" was developed with the intention of addressing the research problem. The results of the research, as assessed by the participants, indicated satisfaction with clear and concise language, an attractive layout, and free access, guiding educators in the use of tools in the classroom. It is essential to go beyond post-pandemic teaching strategies and digital tools, considering the evolving student profile over time. This transformation in the educational model needs to be considered to promote a more comprehensive and lasting digital inclusion.